A educação ambiental crítica e o saber de experiência feito na educação de pessoas jovens e adultas : um diálogo para a transformação - Franco, Flávia Fina (2016)
In this research we seek to investigate a classroom education of young and adult people, in order to know potentialities and obstacles of the articulation proposal between environmental education and this school modality, having as a reference two key concepts: criticity and knowledge of living experience. Studies suggest that the inclusion of socio-environmental theme in education of young and adult people can contribute as much to overcome the compensatory and reductionist view that has marked this modality and for encourage questions and reflections of these people about their roles in the interpersonal relationships, with the world and in the world, to recognize and assume their potential to act in reality. We adopted as reference a critical, dialogic, liberating environmental education, driving of reflections by questioning socio-environmental issues. We opted for education of young and adult people for being a school modality, as well as their subject, has been historically marginalized, marked by unjust and oppressive relations and because we also believe in the potential of these individuals recognizing their experience and their knowledge, knowledge accumulated during their lives, which Freire called knowledge of living experience. So the questions that guide this research are: the knowledge of living experience that has been considered and developed also in the modality of education for young and adult people can contribute to the practice of environmental education? The criticity which has been developed in the field of environmental education can contribute to the practice of education for young and adult people in the school context? For the construction of this study, we conducted an empirical work. The empirical investigation was conducted in a public school in São Paulo State, in which were involved students of education of young and adult people and teachers of this modality with experience in the field of environmental education. Paulo Freire (2005), with the dialogue theory, and Jürgen Habermas (2012a; 2012b), with the theory of communicative action, were authors who guided us to the choice of the critical communicative methodology, which is based on the construction of knowledge through the establishment of inter-subjective dialogue between subjects and from that construction make it possible act in reality, transformed it. Using this methodology, the dialogue breaks with the interpretative and epistemological gaps usually considered and developed among the people of the investigated context and academic people. We use the communicative observation and interview as data collection instruments. In partnership with the students, the data of the observation were analyzed considering the exclusionary and transformative dimensions, its own methodology, in relation to approach between environmental education and education of young and adult people. The informations obtained through interviews were discussed together with teachers, on the dual categorization of social reality in system and world of life, based on Habermas. With the data already analyzed, we found in the context investigated elements like educational practices and attitudes teachers consistent with the reality of students that enhance the inclusion of environmental issues in a critical perspective on the education of young and adult people. On the other hand, were also identified elements such practices and teaching attitudes associated with a model of youth and adult compensatory people education, which hinders said insert, which is necessary for an education committed a social transformation that leads to relationships socially fairer and more environmentally sustainable relations. Finally, we verified the adequacy of a critical environmental education of young and adult people as a potent space of learning and transformations, a space for them to exercise their critical faculties towards their emancipation and thus recognize as historical subjects participants of social-environmental changes.